2010
DOI: 10.1007/s00213-010-2112-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral cortisol impairs implicit sequence learning

Abstract: This study is the first human investigation indicating impaired implicit memory function after exogenous administration of the stress hormone cortisol. This effect may depend on hippocampus engagement in implicit sequence learning, but the involvement of other brain structures is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…For example, a study by Frank et al (2006) showed that the benzodiazepine midazolam, which inactivates the hippocampus, causes explicit memory deficits in healthy participants, but enhances implicit learning. In contrast, a more recent study found impaired implicit learning after the exogenous administration of the stress hormone cortisol (Römer et al, 2011). The engagement of specific brain structures in these phenomena needs to be clarified.…”
Section: Introductionmentioning
confidence: 91%
“…For example, a study by Frank et al (2006) showed that the benzodiazepine midazolam, which inactivates the hippocampus, causes explicit memory deficits in healthy participants, but enhances implicit learning. In contrast, a more recent study found impaired implicit learning after the exogenous administration of the stress hormone cortisol (Römer et al, 2011). The engagement of specific brain structures in these phenomena needs to be clarified.…”
Section: Introductionmentioning
confidence: 91%
“…There are only a few studies investigating the effects of cortisol on implicit memory processes and these showed mixed results [36], [37], [38], [39]. However, as described above, intrusions are thought to rely on implicit memory processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only three studies focused on how stress alters the detection and extraction of different types of regularities from the environment (Römer et al, 2011;King, 2013;Dolfen et al, 2019). In the present study, we aimed to get a better understanding of how stress influences the simultaneous acquisition of statistical and sequential regularities.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, only a handful of studies investigated the effect of stress on the acquisition of statistical or sequential regularities (Römer et al, 2011;King, 2013;Dolfen et al, 2019). In King's (2013) study, participants were exposed to a statistical regularity without being aware that learning were taking place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation